Synthesis and in vitro phantom NMR and MRI studies of fully organic free radicals, TEEPO-glucose and TEMPO-glucose, potential contrast agents for MRI1. Issue 20 (6th March 2015) - Soikkeli, M.; Sievänen, K.; Peltonen, J.; Kaasalainen, T.; Timonen, M.; Heinonen, P.; Rönkkö, S.; Lehto, V.-P.; Kavakka, J. S.; Heikkinen, S.
<x xml:space="preserve">Abstract</x> Two organic radical contrast agents, TEMPO-Glc and TEEPO-Glc, were synthesized and their stabilities and contrast enhancing properties were tested with in vitro NMR and MRI experiments.